2013
DOI: 10.5012/bkcs.2013.34.7.1961
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Asynchronous Proton Transfer in H-Bonding Relay Model: An Implication of Green Fluorescent Protein

Abstract: Theoretical investigations have been performed for the ground state (S 0 ) and the first excited state (S 1 ) of the hydrogen bonded green fluorescent protein (GFP) model. The potential energy surface (PESs) of S 0 was obtained by B3LYP method and that of S 1 was obtained by CIS method. Based on the relative stabilities of species and the energy barriers for the proton transfer, it was found that proton transfer could take place both under the ground state and the first excited state. As determined by the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Including the single barrier, the GSPT reaction should be a concerted and asynchronous process which has been stated in our previous study. 52 It needs to be emphasized that GSPT is a concerted process regardless of the electric eld, owing to the single barrier along the PES (for F x +25.71 and F y +25.71, the GSPT is a barrierless process and without ZPE, all of the PESs have a single barrier). It was further revealed that no intermediates exist through IRC calculations and the TSs are real with only one imaginary vibrational mode from the frequency calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Including the single barrier, the GSPT reaction should be a concerted and asynchronous process which has been stated in our previous study. 52 It needs to be emphasized that GSPT is a concerted process regardless of the electric eld, owing to the single barrier along the PES (for F x +25.71 and F y +25.71, the GSPT is a barrierless process and without ZPE, all of the PESs have a single barrier). It was further revealed that no intermediates exist through IRC calculations and the TSs are real with only one imaginary vibrational mode from the frequency calculations.…”
Section: Resultsmentioning
confidence: 99%
“…However, determining reaction synchronism is extremely hard for experiments, but feasible for computational calculations to obtain intrinsic insight. As we stated in a previous study [35] that the reaction takes place via single/multiple barrier without/with stable intermediates. However, synchronous process means that a chemical process takes place in a synchronous fashion.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, numerous enzyme reactions, such as serine proteases [26], alcohol dehydrogenases [27], and carbonic anhydrases [28], involve MPTs. The processes can occur in either synchronous or asynchronous manner [29–31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous enzyme reactions, such as serine proteases [26], alcohol dehydrogenases [27], and carbonic anhydrases [28], involve MPTs. The processes can occur in either synchronous or asynchronous manner [29][30][31].Water is a widely used model system to investigate the dynamics of MPTs in O H‧‧‧O H-bond networks. A few studies can also be found on the proton transfers in water trimers, tetramers, and pentamer in gas phase [32][33][34][35][36][37][38].…”
mentioning
confidence: 99%